Inventive activity of the Departments of Protein Structure and Function, and Molecular Immunology of the Palladin Institute of Biochemistry of NAS of Ukraine. Part II. National breakthrough in the study and diagnostics of human hemostasis system - N. E. Lugovska (The Ukrainian Biochemical Journal, 2016)
The scientists of Protein Structure and Function, and Molecular Immunology Departments of the Palladin Institute of Biochemistry (NAS of Ukraine) under the supervision of member of NASU and NAMSU, prof. S. V. Komisarenko and corresponding member of NASU prof. E. V. Lugovskoy have made the real breakthrough in the field of research of the mechanisms of fibrin polymerization and formation of fibrin framework of thrombi. The immunodiagnostic test-systems for the evaluation of the risk of thrombus formation were developed for the first time. Researches have obtained the monoclonal antibodies to fibrinogen, fibrin, D-dimer and their fragments. These monoclonal antibodies were used as molecular probes for the localization of newly detected fibrin polymerization sites. Obtained antibodies with high affinity interact with fibrinogen, D-dimer and soluble fibrin – main markers of the risk of thrombus formation. They were used for the development of the immunodiagnostic test-systems to quantify these markers in human blood plasma for the evaluation of the state of haemostasis system, detection of prethrombotic states, disseminated intravascular coagulation, detection of thrombosis and monitoring of antithrombotic and fibrinolytic therapy. The successful trial of developed test-systems was carried out in clinics of Ukraine, and the State registration was obtained for the implementation of them into the clinical practice. Presented works were awarded State prize of Ukraine in Science and technology.